(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study is an attempt to organize a comparison to recognize the points of similarity between both battles Ohud and BalatAshuhada’ from part of causes and results.It had been clear to us that there is some similarity in causes between both battles, for example vengeance and the attempt of compensating a previous loss either it was for Moslems or their antagonists. There was also some similarity in causes of Moslems’ loss, such as violating the military orders, the internal controversy, and the demographic structure of the Moslem’s army, in addition to other causes had been shown in the context of the study.